Perfil de Elementos Metálicos y de Algunos Metaloides en Aguas de Grifo de la Ciudad de Guanajuato - Landero Figueroa, Julio Alberto; Gómez Ojeda, Armando; Wrobel, Kazimierz; Wrobel, Katarzyna (Acta Universitaria, 2008)
In this paper, the concentration levels of metals and metalloids found in tap water in the city of Guanajuato are reported. The quantification was carried out by inductively coupled plasma – mass spectrometry (ICP-MS). The results obtained in the analysis of tap water from 31 sampling sites showed the mean values < 0,2 μg l-1 for Ag, Cd, Co, Se, Th, Tl, U; in the range 0,2 μg l-1– 1,5 μg l-1 for Cr, Hg, Mo, Pb, Sb; in the range 1,5 – 6,0 μg l-1 for As, Mn, Ni, V; in the range 15 μg l-1 – 71 μg l-1 for Ba, Cu y Zn. Based on current Mexican and US regulations (NOM-127 SSA1-1994, USEPA-2006), the results obtained indicate that the tap water in the city of Guanajuato is not contaminated by metals and metalloids. However, in samples from six sites, the concentration levels of mercury were higher than the maximum permissible level regulated by NOM (1 μg l-1).